Complementary Understandings of Availability: Jean Vanier in Conversation with the Philosophers Emmanuel Levinas and Gabriel Marcel. (2nd April 2020) - Matthews, Pia
Abstract: There has been a significant shift in twentieth century philosophy toward 'other-person-ness' where availability and attentiveness to the other seem to have taken central stage. Although not always accepted as philosophers in the conventional sense, the philosophers Emmanuel Levinas and Gabriel Marcel were at the forefront of this new move. This article puts Jean Vanier in conversation with Levinas and Marcel in order to tease out the complementarity of their philosophical approaches. While there is much that the three philosophers have in common, including the question of the relationship of faith to philosophy, there is also a clear progression in thinking. Levinas offers an uncompromising responsibility and availability for the other who remains an 'absolute other'; Marcel reminds that the other is also my neighbor for whom my presence denotes my availability; Vanier in turn adds a radically new dimension. Rather than a one-way street of availability to the other, Vanier opens up a two-way street where the other, who often seems very different, reveals our mutual vulnerability and demonstrates that living by the heart can lead us all to becoming truly human.